2016
DOI: 10.1007/s11199-016-0605-2
|View full text |Cite
|
Sign up to set email alerts
|

What Did He Mean by that? Humor Decreases Attributions of Sexism and Confrontation of Sexist Jokes

Abstract: Sexist humor may be more difficult to confront than serious expressions of sexism because humor disguises the biased nature of the remark. The present research investigated whether delivering a sexist remark as a joke, compared to a serious statement, tempered perceptions that the speaker was sexist which, in turn, made women less likely to confront. Using a computer-mediated instant messaging paradigm, women were randomly assigned to receive the same sexist remark phrased either in a serious manner or as a jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 59 publications
5
49
1
Order By: Relevance
“…Broadly, their results demonstrated that the use of sexist humor led to decreased perceptions of the male humorist as a sexist, as well as a decreased likelihood of confronting that individual for those views. Additionally, the presence of hostile sexist beliefs among the female participants in this investigation exacerbated these effects (Mallett et al 2016; Experiment 2). Research by Woodzicka et al (2015) helps to contextualize these effects.…”
Section: Strategic Humor and Bias Confrontationmentioning
confidence: 72%
See 1 more Smart Citation
“…Broadly, their results demonstrated that the use of sexist humor led to decreased perceptions of the male humorist as a sexist, as well as a decreased likelihood of confronting that individual for those views. Additionally, the presence of hostile sexist beliefs among the female participants in this investigation exacerbated these effects (Mallett et al 2016; Experiment 2). Research by Woodzicka et al (2015) helps to contextualize these effects.…”
Section: Strategic Humor and Bias Confrontationmentioning
confidence: 72%
“…Recent work on the effects of humor on bias confrontation has attempted to fill some of these gaps. For example, Mallett et al (2016) investigated how the use of sexist humor, compared to nonhumorous sexist statements, affected women's likelihood to label a male interaction partner as sexist. Broadly, their results demonstrated that the use of sexist humor led to decreased perceptions of the male humorist as a sexist, as well as a decreased likelihood of confronting that individual for those views.…”
Section: Strategic Humor and Bias Confrontationmentioning
confidence: 99%
“…Finally, they may take a benign response, believing that the perpetrator meant well by the action. For example, the action could be viewed as a joke (Mallett et al 2016 ). Alternatively, women may view sexual objectification as a compliment (Sáez et al 2016 ).…”
mentioning
confidence: 99%
“…On these grounds, it could be argued that humour, with its distracting and resistance-alleviating abilities (e.g. Mallett et al 2016), can assuage the provocative appeals of female-disparaging ads and make them more ethically acceptable. Thus, based on the aforementioned: H3.…”
Section: Humorousness Of the Ad As Moderatormentioning
confidence: 99%